PERENCANAAN PEMBANGUNAN OBJEK WISATA DI DESA KALI KECAMATAN TOMBATU KABUPATEN MINAHASA TENGGARA - MONONEGE, RAVIE GIAN; LENGKONG, FLORENCE; TAMPI, GUSTAAF (Sam Ratulangi University, 2020)
Resources owned by the Indonesian nation need to be optimally utilized through the implementation oftourism in the show to increase the national income in order to improve the welfare and prosperity ofthe people based on the background of the problem then this research aims to know what tourism sectordevelopment planning by the Department of Tourism and Culture, especially in the village Kalisubdistrict Tombatu.The type of research used in this study is a descriptive research study that intends to understand thephenomenon of what is experienced by the research object. The informant in the research was obtainedfrom the field visit to the research site by the researchers, namely in the tourist attractions method ofdetermination of the informant by choosing a resource that really knows about the problems that occurin the natural tourist areas so that they will provide information precisely according to what is requiredby researchersThe results showed that the preparation of the program plan, strategy and operationalplan/Development implementation by the Department of Culture and Tourism of southeast MinahasaRegency refers to the general policy plan of the government as per Act No. 10-year 2009 on tourism.The goal is to make the program plan in the area and its implementation does not overlap but theprogram goes in a direct and aligned starting from the provincial central level to the level of the districtand village.Keywords: planning, development, attraction